Notes on Gyrodactylus gussevi Ling Mo-en, 1962 (Monogenea: Gyrodactylidae) - Ergens, R; Yukhimenko, S S (Folia parasitologica, 1991)
The authors describe a species which is strikingly similar to the species Gyrodactylus gussevi Ling Mo-en, 1962 on the basis of morphometrical evaluation of 6 gyrodactylid specimens found on the fins of Parasilurus asotus (L.) which was captured in the River Amur near Khabarovsk. Due to inaccurate and incomplete original description of G. gussevi, the authors have to determine this species only provisionally as G. gussevi. As a result of evident appurtenance to G. latus--complex, P. asotus seems to be the "wrong" host.
Keywords: Cestoda; ryby; Fishes; Ectoparasitic Infestations; Fish Diseases; Animals; infestace ektoparazity; cestodózy; Cestode Infections; zvířata; nemoci ryb